In Situ Field Sequencing and Life Detection in Remote (79°26′N) Canadian High Arctic Permafrost Ice Wedge Microbial Communities - Goordial, J.; Altshuler, Ianina; Hindson, Katherine; Chan-Yam, Kelly; Marcolefas, Evangelos; Whyte, Lyle G. (Frontiers in Microbiology, 2017)
Significant progress is being made in the development of the next generation of low cost life detection instrumentation with much smaller size, mass and energy requirements. Here, we describe in situ life detection and sequencing in the field soils over laying ice wedges in polygonal permafrost terrain on Axel Heiberg Island, located in the Canadian high Arctic (79°26′N), an analogue to the polygonal permafrost terrain observed on Mars. The life detection methods used here include (1) the cryo-iPlate for culturing microorganisms using diffusion of in situ nutrients into semi-solid media (2) a Microbial Activity Microassay (MAM) plate (BIOLOG Ecoplate) for detecting viable extant microoganisms through a colourimetric assay, and (3) the Oxford Nanopore MinION for nucleic acid detection and sequencing of environmental samples and the products of MAM plate and cryo-iPlate. We obtained 39 microbial isolates using the cryo-iPlate, which included several putatively novel strains based on the 16S rRNA gene, including a Pedobacter sp. (98% closest similarity in GenBank) which we partially genome sequenced using the MinION. The MAM plate successfully identified an active community capable of L-serine metabolism, which was used for metagenomic sequencing with the MinION to identify the active and enriched community. A metagenome on environmental ice wedge soil samples was completed, with base calling and uplink/downlink carried out via satellite internet. Validation of MinION sequencing using the Illumina MiSeq platform was consistent with the results obtained with the MinION. The instrumentation and technology utilized here is pre-existing, low cost, low mass, low volume, and offers the prospect of equipping micro-rovers and micro-penetrators with aggressive astrobiological capabilities. Since potentially habitable astrobiology targets have been identified (RSLs on Mars, near subsurface water ice on Mars, the plumes and oceans of Europa and Enceladus), future astrobiology missions will certainly target these areas and there is a need for direct life detection instrumentation.